Brush of the gods - Look, Lenore; So, Meilo (New York : Schwartz & Wade Books, 2013)
During the Tang dynasty, master painter Wu Daozi creates an extraordinary mural for the emperor.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, May 2013
Kirkus Starred, May 2013
Pub Weekly, April 2013
Keywords: Wu, Daozi, -- 689-759 -- Juvenile fiction; Wu, Daozi, -- 689-759 -- Fiction; Wu, Daozi, -- 689-759 -- Fiction; Artists -- Juvenile fiction; Painting -- Juvenile fiction; Artists -- Fiction; Painting -- Fiction; Artists -- Fiction; Painting -- Fiction; China -- History -- Tang dynasty, 618-907 -- Juvenile fiction; China -- History -- Tang dynasty, 618-907 -- Fiction; China -- History -- Fiction; Picture books for children